Multiplexed Quantification of Proglucagon-Derived Peptides by Immunoaffinity Enrichment and Tandem Mass Spectrometry after a Meal Tolerance Test. (6th January 2020) - Lee, Anita Y H; Chappell, Derek L; Bak, Monika J; Judo, Michael; Liang, Linda; Churakova, Tatyana; Ayanoglu, Gulesi; Castro-Perez, Jose; Zhou, Haihong; Previs, Stephen; Souza, Sandra C; Lassman, Michael E; et al.
Abstract: BACKGROUND: Proglucagon-derived peptides (PGDPs), which include glucagon-like peptide (GLP)-1, glucagon, and oxyntomodulin, are key regulators of glucose homeostasis and satiety. These peptide hormones are typically measured with immuno-based assays (e.g., ELISA, RIA), which often suffer from issues of selectivity. METHODS: We developed a multiplexed assay for measuring PGDPs including GLP-1 (7–36) amide, GLP-1 (9–36) amide, glucagon, and oxyntomodulin by mass spectrometry and used this assay to examine the effect of a meal tolerance test on circulating concentrations of these hormones. Participants fasted overnight and were either given a meal (n = 8) or continued to fast (n = 4), with multiple blood collections over the course of 3 h. Plasma samples were analyzed by microflow immunoaffinity (IA)-LC-MS/MS with an isotope dilution strategy. RESULTS: Assay performance characteristics were examined and established during analytical validation for all peptides. Intra- and interassay imprecision were found to be 2.2%–10.7% and 6.8%–22.5%, respectively. Spike recovery was >76%, and dilution linearity was established up to a 16-fold dilution. Immediately after the meal tolerance test, GLP-1 and oxyntomodulin concentrations increased and had an almost identical temporal relationship, and glucagon concentrations increased with a slight delay. CONCLUSIONS: IA-LC-MS/MS was used for the simultaneous and selective measurement of PGDPs. This work includes the first indication of the physiological concentrations and modulation of oxyntomodulin after a meal.